2020
DOI: 10.1021/acs.nanolett.0c01270
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Flash Memory with a Single-Layer Nanofloating Gate

Abstract: Here we use triple-cation metal–organic halide perovskite single crystals for the transistor channel of a flash memory device. Moreover, we design and demonstrate a 10 nm thick single-layer nanofloating gate. It consists of a ternary blend of two organic semiconductors, a p-type polyfluorene and an n-type fullerene that form a donor:acceptor interpenetrating network that serves as the charge storage unit, and of an insulating polystyrene that acts as the tunneling dielectric. Under such a framework, we realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…[52] Vasilopoulou et al used higher amounts of Rb + salts and reported only p-type operation for Rb 0.15 (MAFA) 0.85 PbI 3 . [153] In 2019, the first transistor based on a low-bandgap mixed lead-tin perovskite layer, that is, FAPb 0.5 Sn 0.5 I 3 was demonstrated (Figure 7c). [111] This device operated at room temperature upon p-type doping with ZnI 2 and yielded a mobility of μ h = 0.007 cm 2 V -1 s -1 and enhanced stability resulting from the reduction in tin-rich clusters.…”
Section: D Hybrid Perovskite Field-effect Transistorsmentioning
confidence: 99%
See 2 more Smart Citations
“…[52] Vasilopoulou et al used higher amounts of Rb + salts and reported only p-type operation for Rb 0.15 (MAFA) 0.85 PbI 3 . [153] In 2019, the first transistor based on a low-bandgap mixed lead-tin perovskite layer, that is, FAPb 0.5 Sn 0.5 I 3 was demonstrated (Figure 7c). [111] This device operated at room temperature upon p-type doping with ZnI 2 and yielded a mobility of μ h = 0.007 cm 2 V -1 s -1 and enhanced stability resulting from the reduction in tin-rich clusters.…”
Section: D Hybrid Perovskite Field-effect Transistorsmentioning
confidence: 99%
“…Gate voltage dependent tunneling of holes from the perovskite into the fullerene:polyfluorene organic blend through the insulating polystyrene component enabled memory transistor operation with a wide operating voltage window and memory on/off ratios as high as 10 7 . The devices exhibited good retention of their programmed state for up to 10 6 s. [153] Gedda et al investigated a blend of (PEA) 2 PbBr 4 :[2,7-dioctyl [1]benzothieno [3,2-b] benzothiophene] (C 8 -BTBT) for memory application. In this 2D Ruddlesden-Popper perovskite, the lead bromide layers separated by the insulating organic cations acted as floating gate and allowed effective trapping/de-trapping of holes depending on the applied gate voltage.…”
Section: Perovskite-based Memory Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the development of cutting‐edge material, optimized memory device structures based on different materials can be fabricated. [ 30,103 ] To simplify the separate deposition process of dielectric layer and floating gate layer, Yan et al. reported a nano‐floating gate memory using ZnSe@ZnS core–shell quantum dots which plays dual roles as discrete charge storage and tunneling centers.…”
Section: Developments and Challengesmentioning
confidence: 99%
“…(G) Plot of write and erase current densities versus time for the evaluation of flash memory retention time. (D)–(G) Reproduced with permission: Copyright 2020, American Chemical Society 73 …”
Section: Organic–inorganic Halide Perovskite Based Neuromorphic Devicesmentioning
confidence: 99%